Pengaruh Financial Distress terhadap Auditor Switching - Syafrita Ridha Ginting; Slamet Sugiri (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2025)
This study aims to examine whether certain financial indicators, previously identified as strong predictors of financial distress, influence auditor switching. The indicators analyzed are return on total assets, net profit on total assets, earnings per share, and cash flow per share. The sample consists of 37 financially distressed companies listed on the Indonesia Stock Exchange, identified using the Altman Z"-Score model, comprising a total of 148 observations. Data analysis was conducted through logistic regression. Findings reveal that return on total assets negatively impacts auditor switching, while net profit on total assets shows a positive effect. However, earnings per share and cash flow per share do not significantly influence auditor switching. These results offer valuable insights for financial statement users and stakeholders in forecasting financial distress in firms that change auditors, thereby supporting critical decision-making for these users.